2004
DOI: 10.1001/archopht.122.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Graded Full-Thickness Anterior Blepharotomy for Upper Eyelid Retraction

Abstract: Background: A chief morbidity of Graves eye disease is upper eyelid retraction that results in exposure keratopathy and cosmetic deformity. Objective: To assess the efficacy of graded anterior blepharotomy to treat upper eyelid retraction. Methods: Fifty eyelids of 32 patients with Graves eye disease-associated upper eyelid retraction, causing symptomatic ocular exposure, were treated with graded, transcutaneous, full-thickness, anterior blepharotomy. Preoperative and postoperative ocular exposure symptoms, up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 24 publications
0
52
0
3
Order By: Relevance
“…Seventy percent of patients (n ¼ 7/10) were euthyroid at the time of surgery and 70% had received steroid treatment for that condition. The average follow-up was 13 months (range [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The indication for eyelid lowering was lagophthalmos in five (42%) (mean degree of lagophthalmos was 1.9 mm (range 1-6.5 mm)), foreign body sensation in eight (67%), photophobia in seven (58%), and symptomatic epiphora in three (25%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seventy percent of patients (n ¼ 7/10) were euthyroid at the time of surgery and 70% had received steroid treatment for that condition. The average follow-up was 13 months (range [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The indication for eyelid lowering was lagophthalmos in five (42%) (mean degree of lagophthalmos was 1.9 mm (range 1-6.5 mm)), foreign body sensation in eight (67%), photophobia in seven (58%), and symptomatic epiphora in three (25%).…”
Section: Resultsmentioning
confidence: 99%
“…Using the graded fullthickness anterior blepharotomy procedure, first communicated by Koornneef in 1999, Elner et al 15 reported an average postoperative MRD of 3.07-3.57 mm and 93% patient satisfaction. A series by Hintschich and Haritoglou 16 reported that 95% of operated lids achieved a 'perfect' or an 'acceptable' result while using full-thickness blepharotomy to treat TED lid retraction, which compares well to the results reported with this technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mullerectomy and levator resection should be used in the case of more severe retraction. Full-thickness blepharotomy also has been described as therapeutic [16]. Lateral flare is treated with lateral dissection of Muller's muscle and release of the lateral horn of the levator aponeurosis between the two lobes of the lacrimal gland.…”
Section: Orbital Decompression Surgerymentioning
confidence: 99%
“…Unfortunately, the basic paradigm of repositioning the insertions of the extraocular muscles has remained unchanged for a century, and in bad Graves' strabismus when the muscles are fibrotic and damaged, even the best strabismus surgery cannot re-create normal fields of binocular vision. Eyelid repositioning surgery has also undergone incremental advances, with smaller incisions (e.g., minimal incision en-glove lysis of the lower eyelid retractors with dermis grafting) (32)(33)(34). Nonsurgical treatment with hyaluronic acid gel may be useful for temporary improvement in some cases (35).…”
mentioning
confidence: 99%